Familial congenital heart disease in Bandung, Indonesia - Sri Endah Rahayuningsih (Indonesian Pediatric Society, 2013)
Background Congenital heart disease (CHD) may occur inseveral members of a family. Studies have shown that familialgenetic factor play a role in CHD.Objective To identify familial recurrences of CHD in familieswith at least one member treated for CHD in Dr. Hasan SadikinHospital, Bandung Indonesia.Methods In this descriptive study, subjects were CHD patientshospitalized or treated from January 2005 to December 2011. Weconstructed family pedigrees for five families.Results During the study period, there were 1,779 patients withCHD. We found 5 families with 12 familial CHD cases, consistingof 8 boys and 4 girls. Defects observed in these 12 patients weretetralogy of Fallot, transposition of the great arteries, persistentductus arteriosus, ventricular septa! defect, tricuspid atresia,pulmonary stenos is, and dilated cardiomyopathy. Persistent ductusarteriosus was the most frequently observed defect (4 out of 12subjects) . None of the families had a history of consanguinity. Therecurrence risk of CHD among siblings was calculated to be 0.67%,and the recurrence risk ofCHD among cousins was 0.16%.Conclusion Familial CHD may indicate the need for geneticcounseling and further pedigree analysis.